A study of campus wireless network technology acceptance among student in UiTM Terengganu, Dungun Campus / Aainaa Abdul Rahim, Nur Izyan Kamaru Zaman and Zaimatul Adawiah Zainuddin - Abdul Rahim, Aainaa; Kamaru Zaman, Nur Izyan; Zainuddin, Zaimatul Adawiah (2012)
This research is about a study on the Campus Wireless Acceptance among UiTM Terengganu, Dungun Campus Students was conducted internally by using the UiTM Dungun students as respondents. The rationale behind the choosing of UiTM Dungun students was to know why students were using Campus Wireless. The use of campus wireless will save time and resource costs and will helps students connect to the Internet and Intranet in open spaces around the campus area. The objective of this study are to investigated the acceptance of wireless LANs among student in UiTM Terengganu, Dungun Campus and also to examine the use of Campus Wireless Local Area Network (WLANs) from perspective of students. This is a research descriptive research, where the purpose of descriptive research is to describes the characteristics of an existing phenomenon. There are around 1500 student of Bachelor Student UiTM Dungun, Terengganu . The sample size is 306 and the unit of analysis is individual with the instrument of Likert Scale Question and Close Ended Question. Questionnaire is used to collect the data and mean analysis is used to analyze the data. There were three variable in the research which is Perceived Ease of Use (PEU), Perceived Usefulness (PU) and Attitude toward New Technology (ATT). From the analysis, all the three variable have higher level of Campus Wireless Acceptance and ail the mean shows the positively acceptance for all questions in the each of variable. From that, its shows a good feedback which means that the respondents accept the use of Campus Wireless LAN that giving them benefits. This research should make a contribution to the understanding of the factors that relate to the student’s Campus Wireless LAN acceptance. This research also assists in identifying whether the objectives of the research have been achieved or not and this research also was able to emphasize the importance of student’s acceptance in using Campus Wireless LAN and related with their education activities during in campus.